Mass-spectrometric study of thermal decomposition of some polyketides in condensed and adsorbed states - Kulik, T. V.; Galagan, N. P.; Pogorelyi, V. K.; Pokrovskiy, V. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
A study has been conducted on adsorption of semisynthetic flavonoid venoruton on the surface of highly dispersed silica (HDS) modified with polyvinylpyrrolidone (PVP). It has been found that an adsorption value of venoruton for the modified silica was 20% higher than that of hydroxylated silica surface. By the temperature-programmed desorption technique with the mass‑spectrometric registration of volatile constituents (TPD MS) a research has also been made into decomposition of venoruton adsorbed by system PVP-HDS. It has been shown that the number of stages of thermolysis of carbohydrate parts of venoruton molecules adsorbed on the modified surface decreases down to one while in the case of the condensed state there are two stages of carbohydrate portion thermolysis and in the situation with the adsorption on the hydroxylated HDS surface there are three stages. As far as the system venoruton-PVP-HDS is concerned, the maximum rate of volatile constituent elimination (destruction of carbohydrate parts of molecules) is shifted towards high temperature region by 130°C in comparison with the condensed state and by 200°C in comparison with the state set up during adsorption on the hydroxylated HDS surface. The increase in the thermal stability of venoruton adsorbed by the PVP-HDS system is related to the effect of PVP polymer chains, which block the access of venoruton molecules to active sites of the silica surface.